The Relevance of the Philosophy of Science in the Era of Artificial Intelligence: An Epistemological Reflection on Digital Truth - Khairatunnisa, Aulia; Darma Putri, Celia; M. Abyadi; Furqon, Mohd; Gustini, Popy; Desyandri (Journal of Practice Learning and Educational Development, 2026)
The rapid development of Artificial Intelligence (AI) has significantly transformed the production and dissemination of knowledge in the digital sphere, while simultaneously raising epistemological concerns regarding truth, validity, and the authority of knowledge. Information generated by AI systems often appears systematic and convincing, which may lead to its being equated with authentic scientific knowledge. This condition highlights the crucial role of the philosophy of science as a reflective framework for critically assessing and distinguishing between AI-generated outputs and genuine knowledge grounded in strong epistemic foundations. This study aims to examine the relevance of the philosophy of science in the era of Artificial Intelligence through an epistemological reflection on digital truth. The research employs a Systematic Literature Review (SLR) method by analyzing national journal articles indexed in SINTA published within the last five years that address philosophy of science, epistemology, AI, and digital truth. The findings indicate that AI-generated outputs are probabilistic and representational in nature, and therefore cannot be equated with scientific knowledge that requires rational, empirical, and methodological justification. The philosophy of science plays an essential role in providing an evaluative framework for assessing claims of digital truth, maintaining academic integrity, and enhancing users’ epistemological literacy in the use of AI. Consequently, an epistemological approach grounded in the philosophy of science is essential for critically understanding and responding to digital truth in the era of intelligent technologies.